A spectroscopic survey of potential energy surfaces for the electronic ground state of the HO2 radical: a correction for the DMBE IV potential - Rio, Carolina (2015)
We propose another approach to put right the DMBE IV potential. An additional gaussian term centered in the well depth can be ¯tted to the spectroscopic data using the Hellmann-Feynman theorem. The corrected DMBE IV potential accurately reproduces the rovibrational spectra keeping the remaining features constant.